MANAJEMEN STRATEJIK PADA ORGANISASI SEKTOR PUBLIK - Kenny Dewi (Center for Economic Studies Universitas Katolik Parahyangan, 2007)
Unsatisfactory that comes from society as public services customer to the public sector organizations' performance causing the need of this sector to reform soon. Negative opinions to the public sector organization at one side and the assumptions that private sector organization management is better than public sector organization in other side causing thought from academicians and practitioners to adopt private sector's management approaches. One of those approaches is strategic management that is usually applied in private sector institutions. There are some adaptations have to be considered while adopt strategic management, considering characteristic differences between public and private sector organizations. New Public Management (Christopher Hood, 1991) and Reinventing Government (David Osborne and Ted Gaebler, 1992) are two concepts that viewed as a form of public management and administration modernization or reformation.